Faktor-Faktor yang Berhubungan dengan Perilaku Penggunaan APD pada Pekerja di Proyek Lippo Thamrin Office Tower PT Wijaya Karya Jakarta - Nerti Yunita Sari; Elwindra Elwindra (STIKes Persada Husada Indonesia, 2019)
The use of Personal Protective Equipment (PPE) is the final stage of hazard control, although the use of PPE will be maximized if carried out with other controls, such as elimination, substitution, engineering and administrative controll. This study aims to determine the relationship of factors related to employee behavior in using PPE on workers in the Lippo Thamrin Office Tower Project PT Wijaya Karya. The benefits of using PPE when working are huge in preventing work accidents, but in reality there are still many workers who do not use PPE when working. The design of this study was a descriptive study with a quantitative approach using the Cross Sectional Study method. The number of samples taken was 60 people selected using the Accidental Sampling technique. Data were analyzed using Chi Square. The results showed that there was a significant relationship between Knowledge (P-value = 0.001), Attitude (P-value = 0.002), and Availability of PPE (P-value = 0.047) with the use of PPE. It can be said that workers with good knowledge, positive attitudes, and available PPE tend to use PPE in full. Suggestions to companies to increase workers 'knowledge about occupational hazards and risks, and improve workers' attitudes towards the use of PPE, and conduct PPE procurement with good standards.